On the Alteration of Money – Part 2 - Mariana, Juan de (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2014)
Mariana thoroughly discusses all the problems caused by the change in copper coin, does the same for the silver coin, showing that, by having higher quality and also the issue of supply compared to gold and copper, the damage caused by this practice are larger than those caused in the case of copper. Then discusses the golden money and finally criticizes the practice of the princes of spending the money of his subjects.